2018
DOI: 10.3389/fimmu.2018.02141
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Inhibition of Pro-atherogenic Gene Expression by Multi-STAT Targeting Compounds as a Novel Treatment Strategy of CVDs

Abstract: Cardiovascular diseases (CVDs), including atherosclerosis, are globally the leading cause of death. Key factors contributing to onset and progression of atherosclerosis include the pro-inflammatory cytokines Interferon (IFN)α and IFNγ and the Pattern Recognition Receptor (PRR) Toll-like receptor 4 (TLR4). Together, they trigger activation of Signal Transducer and Activator of Transcription (STAT)s. Searches for compounds targeting the pTyr-SH2 interaction area of STAT3, yielded many small molecules, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Analysis of the corresponding total binding score values (BS) and CBAVs of STATTIC and STX-0119 calculated for each individual STAT, points to their equal binding affinities for STAT1, STAT2, and STAT3 (222). In the same study, we described a novel pan-STAT1/2/3 inhibitor, C01L_F03, with similar characteristics (225). We proposed that this novel class of inhibitors could be implemented in a multi-STAT inhibitory strategy with great promise for the treatment of Cardiovascular diseases (CVDs) (225).…”
Section: A Direct Irf-targeting Strategy To Identify Specific- and Pamentioning
confidence: 94%
See 1 more Smart Citation
“…Analysis of the corresponding total binding score values (BS) and CBAVs of STATTIC and STX-0119 calculated for each individual STAT, points to their equal binding affinities for STAT1, STAT2, and STAT3 (222). In the same study, we described a novel pan-STAT1/2/3 inhibitor, C01L_F03, with similar characteristics (225). We proposed that this novel class of inhibitors could be implemented in a multi-STAT inhibitory strategy with great promise for the treatment of Cardiovascular diseases (CVDs) (225).…”
Section: A Direct Irf-targeting Strategy To Identify Specific- and Pamentioning
confidence: 94%
“…In the same study, we described a novel pan-STAT1/2/3 inhibitor, C01L_F03, with similar characteristics (225). We proposed that this novel class of inhibitors could be implemented in a multi-STAT inhibitory strategy with great promise for the treatment of Cardiovascular diseases (CVDs) (225). Accordingly, blocking of IRF-DNA binding by IRF-specific or pan-IRF inhibitors presents itself as a promising therapeutic tool to combat a wide range of immunological diseases.…”
Section: A Direct Irf-targeting Strategy To Identify Specific- and Pamentioning
confidence: 94%
“…However, recent studies have found that it is also involved in maintaining starter cells in leukemia and colon cancer metastasis ( 64 , 65 ). It was found that blocking STAT3 activity may be an effective strategy for treating CAD ( 66 ). STAT3 is often over-activated in various cancers and is associated with tumor immunosuppression and poor prognosis ( 67 ).…”
Section: Discussionmentioning
confidence: 99%
“…The signal transducer and activator of transcription (STAT) family includes STAT1, STAT2, and STAT3, which transmit signals from the proinflammatory cytokines interferon (IFN)α and IFNγ and pattern recognition receptor (PRR) Toll-like receptors, which are found in blood vessels. An inflammatory environment is formed under the vessel membrane to promote atherosclerosis 61 , 62 . The transcription factor ERG is essential for endothelial homeostasis, driving the expression of lineage genes and suppressing proinflammatory genes, all of which are associated with atherosclerosis 63 , 64 .…”
Section: Disscussionmentioning
confidence: 99%